Poverty Reduction as a Corporate Social Responsibility Agenda: The case of the European Commission - Manca, Christine (2009)
This research attempts to bring some light on the opportunities for the European Commission (EC) to encourage European businesses working in developing countries to make poverty reduction an institutionalised and explicit part of their CSR agenda.